Agricultural Research Investments in Sub-saharan Africa - Recent Trends - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
This article reviews the major investment and institutional trends in agricultural research in sub-Saharan African (SSA) since the early1970s, drawing directly on a new set of data for the 1990s developed through a comprehensive survey conducted in 27 cou